Characteristics of reactivity controlled combustion with n-heptane low temperature reforming products. (1st September 2020) - Zhong, Shenghui; Zhang, Fan; Du, Qing; Peng, Zhijun
Highlights: Direct numerical simulation and homogenous reactor are used to analyze the ignition characteristics. Low temperature reforming products can retard or promote ignition. The Negative Temperature Coefficient behavior is weakened with reforming products. Chemical reaction path way analysis of OH and HO2 is performed to identify the production and consumption source. The heat release from reforming products involved chemical reaction is the key factor to promote the ignition. Abstract: This paper presents a comprehensive study of the effects of n-heptane low temperature reforming (LTR) products on n-heptane/LTR products ignition characteristics by two-dimensional direct numerical simulation (2-D DNS) and zero-dimensional (0-D) reactor under advanced compression ignition engine-like conditions. N-heptane/LTR products reactivity controlled compression ignition is a concept based on "single-fuel" reactivity controlled compression ignition. Two reforming gas compositions are obtained through a reforming-cooling combined process, and the parent fuel (n-heptane) conversion rates are 66.0% and 85.6%, respectively. LTR products are found to retard or promote the ignition depending on the initial mixture composition and temperature in both 2-D DNS and 0-D reactor. Particularly, 0-D results show that LTR products will suppress the ignition event at low initial temperature, while with more n-heptane addition, LTR products will help to shorten the ignition delay time. Moreover, the Negative Temperature Coefficient (NTC) behavior is weakened with LTR products, and this phenomenon is more obvious with higher degree LTR products. Finally, based on the chemical reaction pathway analysis, it is found that the onset of low temperature ignition is advanced in the presence of LTR products, but it may delay the high temperature ignition (HTI). The basic reason of LTR products effect on HTI attributes to heat accumulation in the early phase. This heat accumulation depends on not only the production of active radicals before the crossover temperature around 1000 K, but also the competition of active radicals between LTR products and n-heptane.